Can Humanizing Classroom Meet EFL Learners’ Needs? - Nur Muthmainnah; Muhamad Hasbi (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Humanizing classroom is a learning model which emphasizes the students’ involvement in the classroom and considers the students’ characters, learning style, and background in every phase of teaching-learning activities. This descriptive study investigates the implementation of humanizing classroom practices by high school EFL teachers and looks for the kinds of humanism values being applied as well as their impacts on their pedagogical practices. The subjects of this study were six English teachers at MAN Salatiga. The data is gathered from classroom observation, interviews, and documents. The finding shows that humanizing classroom values is reflected in every aspect and phase of the EFL teaching-learning process, where teachers do not only apply the values during the teaching-learning activities but also in their lesson plan and evaluation. Secondly, positive impacts from the practice exist, proven by the positive feelings shown by the teachers (appreciated) and the students (more confident and comfortable) in their English classes. In addition, when teachers implement the humanizing classroom, students could freely share what they need and feel in the EFL classroom.